External magnetic field-induced circularly polarized luminescence and electroluminescence from optically inactive thermally activated delayed fluorescence material 4CzIPN - Kuroda, Takumi; Kitahara, Maho; Yagi, Shigeyuki; Imai, Yoshitane (Frontiers in Chemistry, 2023)
An achiral optically inactive organic luminophore, 4CzIPN, exhibits circularly polarized thermally activated delayed fluorescence when photoexcited under an external magnetic field. By embedding this luminophore in an active emission layer, an external-magnetic-field-induced circularly polarized electroluminescent device is developed in this study. The Faraday geometry of the applied magnetic field completely controls the direction of rotation of 4CzIPN-derived circularly polarized luminescence and electroluminescence. This is a provisional file, not the final typeset article the small energy gap between singlet and triplet excitation states facilitates endothermic conversion of the triplet to singlet exciton via an inverse intersystem crossing (